PENINGKATAN AKTIVITAS BELAJAR SISWA MENJAHIT CELANA PANJANG PRIA KELAS XII MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DI SMK N 1 KABUPATEN TEBO - Hidayanti, Ratumas; Katin, Yusmar Emmy; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This study reveals about increasing student activity in learning to sew trousersXII class men with type group cooperative learning model investigation at SMK N 1Tebo regency, which in terms of 4 indicators such as: (1) visual activities, (2) oralactivities, (3 ) motor activities, (4) emotional activities. This study is an actionresearch group using a type of investigation with a sample of 16 people.Implementation research through 2 cycles with 3 times face to face. Data collectiontechniques using observation sheets and field notes data analysis techniques using twomethods, namely quantitative and qualitative. The results showed an increase instudent learning activities in learning to sew trousers men using cooperative learningwith group investigation, in siklus I the presentation showed 63% and advance insiklus II showed 83%.